2023
DOI: 10.1159/000528117
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Blood Pressure Is Associated with Increased Brain Amyloid Load in Mild Cognitively Impaired Participants: Alzheimer’s Disease Neuroimaging Initiatives Study

Abstract: <b><i>Background:</i></b> Cardiovascular disease (CVD), including elevated blood pressure (BP), is known to promote Alzheimer’s disease (AD) risk. Although brain amyloid load is a recognized hallmark of pre-symptomatic AD, its relationship to increased BP is less known. The objective of this study was to examine the relationship of BP to brain estimates of amyloid-β (Aβ) and standard uptake ratio (SUVr). We hypothesized that increased BP is associated with increased SUVr. <b><i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…In line with these findings, our study showed a similar effect, where higher BP was associated with myelin reduction and cortical thinning 93 . Furthermore, our findings indicated a significant association between the brain pattern, disease progression and hypertension, aligning with existing research in this field 94,95 .…”
Section: Discussionsupporting
confidence: 91%
“…In line with these findings, our study showed a similar effect, where higher BP was associated with myelin reduction and cortical thinning 93 . Furthermore, our findings indicated a significant association between the brain pattern, disease progression and hypertension, aligning with existing research in this field 94,95 .…”
Section: Discussionsupporting
confidence: 91%